Interpretation of the Verses of Istighfar of the Believers: Study of Tafsir al-Maraghi - Oktavia Dian Riski; Faridah Abduhu; Fajar Novitasari (Al-Shamela : Journal of Quranic and Hadith Studies, 2024)
Every believer who commits a sin, Allah always commands to say istighfar as a way to erase the sin. It is important to study from the perspective of the Qur'an how the interpretation of the verses of istighfar can help erase every sin if practiced. This article aims to discuss the verses of istighfar for believers in the perspective of Tafsir al-Maraghi. By using qualitative methods and descriptive analytical library research, this article examines the verses of istighfar by referring to the book Mu'jam al-A'lam which found seven verses that are in line with this discussion. The article concludes that al-Maraghi's interpretation of the verses of istighfar provides an understanding of the importance of always saying istighfar. Al-Maraghi explains the position of istighfar not only as a suggestion to erase sins, but also equal to repentance, istighfar is more important than asking for victory, the position of istighfar as a veil, the position of istighfar when the situation is difficult is the best time, the position of istighfar as a form of compassion and the position of istighfar as a way to be facilitated in hisab. Of course, the meaning of istighfar by al-Maraghi can be used as a guide for believers to always introspkesi themselves by saying istighfar to Allah SWT.